Stress to Endoplasmic Reticulum of Mouse Osteoblasts Induces Apoptosis and Transcriptional Activation for Bone Remodeling - Hamamura, Kazunori (2007)
ATF4 is an essential regulator in osteogenesis as well as in stress responses to the endoplasmic reticulum (ER). We addressed a question: Does ER stress to osteoblasts upregulate ATF4 expression? If so, do they exhibit ATF4-mediated bone remodeling or apoptosis? ER stress, induced by Thapsigargin and tunicamycin, elevated a phosphorylated form of eIF2α and ATF4, but the cellular fate depended on treatment duration. The treatment for 1 h, for instance, activated Runx2, and type I collagen, while the treatment for 24 h induced apoptosis. Our observations suggest that there is a threshold for ER stress and osteoblasts present a bi-phasic pattern of their fate.